PEMAKNAAN PASANGAN USIA MUDA TERHADAP PROGRAM KELUARGA BERENCANA UNTUK MENINGKATKAN KUALITAS KELUARGA DI KOTA PALEMBANG - Retna Mahriani; Oemar Madri Bafadhal; Nurly Meilinda (Metacommunication: Journal of Communication Studies, 2020)
The advancement of Palembang City family planning programs was not followed by community participation in this program, particularly by young spouses. This is a fascinating topic of discussion as the government's failure in identifying the causes of the decrease in the participation rate in family planning would have consequences for choosing alternative policies and the policy targets are not eventually reached. Therefore, this study aims to provide alternative viewpoints in looking at options for not participating the family planning program, through the meaning of young spouses to the program. This study used a qualitative design by interviewing five young spouses. By using the theory of symbolic interactionalism, this research found that from the dimension of mind, children are an investment that can strengthen their relationship with God while lightening their lives in their pension time. While from the dimension of self, a spouse does not show spontaneity, impulsive, and creative as an individual, but shows themselves as a husband and wife where the decision is in a joint decision. Lastly, from the dimension of society, the informants tend to be closed in making decisions. In more detail, they decide based on the information they know. This indicates the ineffectiveness of information dissemination from government, religious leaders and the mass media. The practical implications of this research are meaning of the individual intersects with the community, so the government must improve the dissemination of information, more holistically, so that messages do not reach only the individuals concerned but the community at large. The results could be the key to enhancement of quality family in Palembang.